The fragment 279 ab of the Forma Urbis Romae A proposal for the partial demolition of Regina Coeli (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2017)
Following an established methodology, the study of the formation process of the urban fabric of a complex and multi-layered context such as Rome, allowed us to position the fragment 279 ab of the Forma Urbis Romae and to understand the history of the site as the necessary premise to its contemporary transformation. The paper examines in detail the formation process of Via della Lungara, in particular of the block now occupied by the Regina Coeli prison. We inferred the rules for the contemporary design from the analysis of the formation process of urban tissues, following the prevision of the dismantling of the prison. This hypothesis, proposed for the first time by the governorate of Rome in 1930, has been waiting for nearly a century. It is necessary to verify different strategies for the transformation of the Regina Coeli prison: is it preferable to recover the old buildings, or to propose the partial or total demolition of the complex for a complete re-design of the urban fabric of the area? A design proposal, based on the partial demolition of the old buildings, is exposed. Despise the new type adopted for the prison design, we found some elements of continuity with the former monastery of Regina Coeli and adopted them as the base of the contemporary design.